Brazil in the 21st century: How to escape the high real interest trap? - Márcio G. P. Garcia (Pontifícia Universidade Católica do Rio de Janeiro (PUC-Rio), Departamento de Economia, 2002)
The hope that lower real interest rates and higher growth would follow the floatation of the currency was in large measure frustrated. Two international liquidity crises, caused by the reversal of capital flows, hit in 2001 and 2002. These crises were associated with higher interest rates, lower economic activity and higher inflation. Therefore, the name exchange-rate stagflation seems to characterize the essence of the phenomenon. A stylized model, due to Caballero and Krishnamurthy [2002], was used to explain the events. The main characteristic of the model is that domestic investment depends on the aggregate international liquidity of the economy, which is a limiting factor. During a liquidity crisis, the amount of liquidity is reduced, and the economy falls in recession. Neither the fiscal authority nor the monetary authority can reflate the economy by increasing government expenditures or the money supply. The bulk of the difficulties Brazil is currently facing derives from the uncertainty associated with the course of the future economic policy to be followed by the new administration, and to the sustainability of the public debt. To avert a painful default, real interest rates must fall and sustained growth must resume. To increase the chances of success, several policy measures are suggested: · To increase the exportability of the economy; · To increase the fiscal effort, in order to help dispel the doubts over the sustainability of the public debt; · To increase the credibility of the monetary authority, by conferring instrument independence to the Brazilian Central Bank; and · To resume the debt management efforts to lengthen the debt profile while reducing the indexation to the exchange rate and to the Selic short term rate, by making larger user of inflation-linked bonds. When and if the current international liquidity crisis is overcome, the above measures will help Brazil to lower the real interest rates and achieve sustained growth.
Keywords: 330; Realzins; Flexibler Wechselkurs; Geldpolitik; Brasilien; Mundell-Fleming-Modell